Los páthe en la Retórica de Aristóteles (Argos, 2025)
This paper intends to present –at least schematically– the structure and the scope of the semantic field "páthos", such as it appears sketched in the second book of Aristotle's Rhetoric. There are two determining facts in the organization of the mentioned semantic field: i) that these páthe are defined as those states through which men suffer an alteration that could change their judgments, and are accompanied by pain (lýpe) and pleasure (hedoné); ii) their definitions mostly include the word 'pain'.
Keywords: semantic field; pathos; rhetoric; lexeme; pain